6=6(x+5)-2x

Simple and best practice solution for 6=6(x+5)-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=6(x+5)-2x equation:


Simplifying
6 = 6(x + 5) + -2x

Reorder the terms:
6 = 6(5 + x) + -2x
6 = (5 * 6 + x * 6) + -2x
6 = (30 + 6x) + -2x

Combine like terms: 6x + -2x = 4x
6 = 30 + 4x

Solving
6 = 30 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6 + -4x = 30 + 4x + -4x

Combine like terms: 4x + -4x = 0
6 + -4x = 30 + 0
6 + -4x = 30

Add '-6' to each side of the equation.
6 + -6 + -4x = 30 + -6

Combine like terms: 6 + -6 = 0
0 + -4x = 30 + -6
-4x = 30 + -6

Combine like terms: 30 + -6 = 24
-4x = 24

Divide each side by '-4'.
x = -6

Simplifying
x = -6

See similar equations:

| (3x+7)=(5x-3) | | 14=x*26 | | 2(x+7)+6=26 | | (5x-1)=(6x-3) | | 2=5(x+9)8x | | T=p-ir | | 4a^2-147=a^2 | | (y-2)-(y+1)=(y-3)-2 | | y=arcsen(3x) | | -(2x+5)=-21 | | 5/8m=60 | | 7-6/5x=8 | | 2(n)+5=45 | | 3x+1-2=7-2 | | log(x)+0.5*x-1=0 | | ln(x)+0.5*x-1=0 | | Y=7/4x-6 | | 4n-7n=-2 | | 3x-3=5y+1 | | Tg(4x)=0.1 | | 11b-2b=72 | | y=arcsen(2x) | | http://www.thelearningodyssey.com/Assess/DPT/QIEImagesStorage/AQ5MA/AQ5MA_MA55212_12_stem1_1.gif | | -1/9t=8 | | 3sin(x+10)=4cos(x-10) | | 5x-3(2x+1)=21+x | | 4x+10+3x=37x | | X^2+y^2+z^2=77 | | (5x-3y)(2x-4y)=0 | | 8-7a=-6a+8 | | 2x-3x+x= | | 6x-14x+16=46 |

Equations solver categories